Efficacy and safety of regorafenib versus dinutuximab with chemotherapy in Chinese children with neuroblastoma - Kun Dong; Guan Wang; Zeng Liang Wang; Xueyan Wang (Bangladesh Pharmacological Society, 2019)
The objective of the present study was to evaluate the efficacy and safety of regorafenib in comparison with dinutuximab with chemotherapy in Chinese children with advanced neuroblastoma. The patients aged less than 16 years who were histologically diagnosed with advanced neuroblastoma were enrolled and randomized to receive either regorafenib plus best supportive care or dinutuximab plus chemotherapy plus best supportive care in a 1:1 ratio. The tumor response assessment was made in accordance with modified international neuroblastoma response criteria. Adverse events were also assessed. Regorafenib showed prolonged overall survival and progression-free survival than who received dinutuximab plus chemotherapy (overall survival: median 32.3 months versus 27.2 months; hazard ratio = 0.45; 95% CI 0.11-0.13, p<0.001; progression-free survival: stratified hazard ratio = 0.48; 95% CI 0.11-0.14; p<0.01).  Moreover, the overall response rate was greater in patients treated with regorafenib as compared to dinutuximab group. Rego-rafenib appears efficacious and has a manageable safety profile in Chinese children with advanced neuroblastoma.